2011
DOI: 10.1111/j.1741-2358.2011.00541.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment, the Mini‐Mental State Examination and socio‐demographic and dental variables in the elderly in Brazil

Abstract: Cognitive impairment, the Mini-Mental State Examination and socio-demographic and dental variables in the elderly in BrazilBackground: Dementia, a syndrome characterised by multiple cognitive impairments, is an increasing medical and social problem across the world. The Mini-Mental State Examination (MMSE) is the instrument most often used in the evaluation of cognitive compromise and dementia in elderly individuals. It is noteworthy that there is a scarcity of works in the literature on the dimensions of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…5 But Brazil has the lowest life expectancy free of CI even among countries in Latin America and the Caribbean. 6 Previous research has shown that CI rates in Brazil vary from 5% among older adults, aged 60 years and older, who are not institutionalized 7,8 to 12% among those institutionalized. 9 Recent estimates indicate that life expectancy with CI decreased between 2000 and 2010 in Brazil, whereas life expectancy without CI increased, which indicates a compression of morbidity during the period.…”
mentioning
confidence: 99%
“…5 But Brazil has the lowest life expectancy free of CI even among countries in Latin America and the Caribbean. 6 Previous research has shown that CI rates in Brazil vary from 5% among older adults, aged 60 years and older, who are not institutionalized 7,8 to 12% among those institutionalized. 9 Recent estimates indicate that life expectancy with CI decreased between 2000 and 2010 in Brazil, whereas life expectancy without CI increased, which indicates a compression of morbidity during the period.…”
mentioning
confidence: 99%
“…Cognitive impairment is a common phenomenon that occurs with age and its global prevalence is increasing significantly 27,28) . This study aimed to determine whether masticatory discomfort in the Korean elderly increases the risk of CD-related DLD and whether there is a difference in risk according to gender and age.…”
Section: Discussionmentioning
confidence: 99%